Arts in Conversation. Leopold Buczkowski’s Artistic Achievement - Staroń, Justyna ((Dif)fusions: Relations between Literature and Art in Poland after 1945, 2019)
The article presents an overview of various artistic activities that Leopold Buczkowski (1905–1989) – who was mainly known for his writing – dealt with. Until now, these activities have been almost completely ignored in academic or popular analysis concerning this artist. These engagements include: painting, illustration, sculpture, music and, to a lesser extent, film and photography. Each of these areas has been are briefly characterized in the article.